Determinants of unsafe behavior among welding workers: A narrative review of occupational safety and health perspectives - Irma Purnama Sari; Marthia Ikhlasiah (Privietlab, 2026)
Occupational Safety And Health (OSH) represents a systematic approach designed to protect workers physical and psychological well-being while promoting a safe and productive work environment. The implementation of OHS principles aims to minimize occupational risks, improve work performance, and prevent workplace accident. In general, occupational accident arise from two primary sources, namely unsafe actions performed by workers and unsafe conditions present in the work environment. Both factors contribute significantly to the occurrence of work-related incidents and injuries. occupational accident because it increases workers exposure to various workplace hazard and reduces compliance with established safety procedures. Such behavior aray include neglecting safety regulations, operating defective equipment, working in hazardous areas without adequate protection, and failing to wear appropriate work attire. These actions can significantly increase the likehood of occupational injuries and accidents. Therefore identifying the factors associated with unsafe behavior is essential for improving workplace safety performance. This studyaimed to examine factors related to unsafe behavior among workers through a literature review approach. Data were collected from 10 scientific articles obtained from Google Scholar, Researchgate, Springer, and other reputable journal databes published between 2019-2026. The findings revealed that several factors are associated with unsafe behavior, including workers attitudes, levelof knowledge, personal characteristics, and the availability of personal protective equipmet (PPE). These factors play an important role in shaping workers compliance with occupational safety practices. Unsafe behavior is influenced by multiple individual and workplace related factors. Consequently, organizations are encouraged to ensure the availability of adequate PPE, provide regular occupational safety training, and strengthen safety supervision to minimize unsafe behavior and reduce the risk of workplace accident.